DAMPAK INDONESIAN CORPORATE SOCIAL RESPONSIBILITY (CSR) AWARD TERHADAP ABNORMAL RETURN DAN TRADING VALUE ACTIVITY (Studi Pada Perusahaan Pemenang Indonesian CSR Award Periode 2005 dan 2008) - -, Supatmi; Idealfa, Neogo Dwianka (Jurnal Manajemen dan Keuangan, 2011)
This research studies the impact of Indonesian Corporate Social Responsibility (CSR) Award to abnormal return and trading value activity. The impact of award publication could be seen from the differences between abnormal return and trading value activity with the Indonesian CSR award announcement. This research samples are 9 companies which accept the appreciation of Indonesian CSR award period 2005-2008 that listed in Indonesia Stock Exchange (IDX). The research data that used is secondary data that consist of daily closing price of share and daily trading volume with an estimation period during 30 days and event period 11 days by using market model and hypothesis research using Wilcoxon Sign Test. The result of this research proves that there are significant differences between abnormal return and trading value activity around the announcement date of Indonesian CSR award.Keywords: Corporate Social Responsibility, Abnormal Return, Trading Value Activity